2023
DOI: 10.1186/s13229-022-00536-z
|View full text |Cite
|
Sign up to set email alerts
|

CRISIS AFAR: an international collaborative study of the impact of the COVID-19 pandemic on mental health and service access in youth with autism and neurodevelopmental conditions

Abstract: Background Heterogeneous mental health outcomes during the COVID-19 pandemic are documented in the general population. Such heterogeneity has not been systematically assessed in youth with autism spectrum disorder (ASD) and related neurodevelopmental disorders (NDD). To identify distinct patterns of the pandemic impact and their predictors in ASD/NDD youth, we focused on pandemic-related changes in symptoms and access to services. Methods Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Due to the recency of the COVID-19 pandemic, literature on its impact on families of children with autism or another DD is limited ( 14 , 15 ). Some studies have documented intensified psychological and behavioral symptoms in children with autism ( 16 19 ), which could potentially be associated with increased parental stress or depression ( 17 , 18 , 20 , 21 ). Several studies have found the COVID-19 pandemic to be associated with decreased quality of life or well-being for autistic individuals and their families ( 16 , 22 ) and increased financial burden ( 21 , 23 ), particularly in Black families ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recency of the COVID-19 pandemic, literature on its impact on families of children with autism or another DD is limited ( 14 , 15 ). Some studies have documented intensified psychological and behavioral symptoms in children with autism ( 16 19 ), which could potentially be associated with increased parental stress or depression ( 17 , 18 , 20 , 21 ). Several studies have found the COVID-19 pandemic to be associated with decreased quality of life or well-being for autistic individuals and their families ( 16 , 22 ) and increased financial burden ( 21 , 23 ), particularly in Black families ( 24 ).…”
Section: Introductionmentioning
confidence: 99%